Antimicrobial Activities of the Lichens Hypogymnia vittata, Hypogymnia physodes and Hypogymnia tubulosa and HPLC Analysis of their Usnic Acid Content - Cansaran-Duman, Demet; Cetin, Demet; Simsek, Husniye; Coplu, Nilay (Asian Journal of Chemistry, 2010)
The aim of present study is to determine the potential antibiotic properties of three lichen species from the Turkey. The acetone extracts obtained from the Hypogymnia vittata, Hypogymnia physodes and Hypogymnia tubulosa were evaluated for antimicrobial activity against 7 bacteria including Escherichia coli (ATCC 35218), Enterococcus faecalis (RSKK 508), Proteus mirabilis (Pasteur Ens. 235), Staphylococcus aureus, Bacillus subtilis, Bacillus megaterium, Pseudomonas aeruginosa. The inhibition zone diameter was determined for each extract using the agar diffusion method and quantitative analysis of usnic acid in these species was achieved using HPLC. Among the Hypogymnia species, maximum activity was observed in H. tubulosa. Usnic acid contents of tested Hypogymnia species was determined to vary between 0.63-2.40 % of dry weight.